The location of financial sector FDI: Tax and regulation policy - Merz, Julia; Overesch, Michael; Wamser, Georg (Journal of Banking & Finance, 2017)
This paper analyzes how corporate taxation and regulatory requirements affect the location of financial sector FDI. We use novel information on new financial services entities established by multinational firms in 83 host countries. We find a negative effect of host country taxes on the probability of choosing a particular host location. We can also confirm a significant influence of the regulatory environment. For example, stricter (equity) capital requirements negatively affect location probabilities. Our empirical approach allows us to provide new insight in how a policy measure of a given country affects other countries by estimating cross-country tax and regulation elasticities.